Dietary silver nanoparticles as immunostimulant on rohu (Labeo rohita): Effects on the growth, cellular ultrastructure, immune-gene expression, and survival against Aeromonas hydrophila - Omoniyi Michael Popoola; Bijay Kumar Behera; Vikash Kumar (Fish and Shellfish Immunology Reports, 2023)
The current study aimed at assessing the immunostimulatory properties of silver nanoparticles (AgNPs) on Labeo rohita, and understanding how it affects the growth, cellular ultrastructure, the expression level of immune genes, and infection risk from Aeromonas hydrophila. Fish (avg wt: 30.1±3.26 g) were fed diets with four separate AgNP inclusion levels (0 µgKg−1 [basic diet, T1], 10 µgKg−1 [T2], 15 µgKg−1 [T3], and 20 µgKg−1 [T4]) for 56 days. After the feeding trial, growth, histological, immunological parameters, and protective immune response against A. hydrophila were assessed. The fish in the treatment groups including T1(control), the T3 growth indices, such as specific growth rate (7.56±0.26) and percent weight gain (231.05±3.21), was statistically higher (P < 0.05). In the immunological and oxidative parameters, levels of SOD and catalase decreased in correlation with a rise in the inclusion doses of AgNP in the liver, and a reduction in catalase values was recorded in the gill. With the addition of AgNP, the NBT value was decreased in the gill, and T3 had a considerably larger (P<0.05) value in the liver (0.493±0.02). The kidney of the L. rohita fed AgNP (0 and20 µgKg−1 AgNP) showed expansion through Bowman's gaps, severing of glomeruli with haemorrhage, as well as atrophic spots between its gaps. The liver showed fibrosis, karyolysis, and the removal of the hepatocytes wall. The gill, liver, kidney, and muscle of fish-fed diets supplemented with AgNP, showed that interleukin-8 (IL-8), and cyclooxygenase-2 (COX-2), were up-regulated. Expression was considerably higher in T3 compared with the control. However, the control group that wasn't given AgNP supplemented diet had increased levels of TGF-beta. Additionally, fish on the T3 diet showed much greater post-challenge survival rates (90%). These findings strongly suggest that dietary inclusion of AgNP (at 10 and 15 µgKg−1 feed) enhances growth, health, and protective immune response against A. hydrophila.